HIV-1 Intersection with CD4 T Cell Vesicle Exocytosis: Intercellular Communication Goes Viral - Soares, Helena (Frontiers in Immunology, 2014)
In cells of the immune system the secretion of extracellular vesicles is modulated through cellular activation. In particular, T cell activation is achieved through cell-cell contacts with antigen presenting cells and the consequent formation of a specialized signaling junction called the immunological synapse. Recent works on CD4 T cells have elucidated that cognate antigen recognition by the T cell receptor (TCR) engages two distinct exocytic events. The first, involves the exocytic targeting of signaling molecules at the synaptic membrane and drives the functional architecture of the immunological synapse. The second, enlists the extracellular secretion of the TCR itself, once the functional architecture of the immunological synapse is accomplished. HIV-1, a human lymphotropic virus, has evolved sophisticated mechanisms to co-opt CD4 T cell physiology. Notably, it has become apparent that HIV-1 intersects the regulated secretory system of CD4 T cells in order to bud from the plasma membrane of the infected cell and to promote bystander cell death. Here, I review the relevance of CD4 vesicle exocytosis to immune regulation and to HIV-1 pathogenesis and discuss their potential therapeutic applications.